Analysis Of Transcriptomic Changes In Oil Palm (Elaeis Guineensis Jacq.) Root Upon Inoculation With Bacillus Sphaericus Upmb10 Using Cdna Microarray - Lim, Kok Ang (2008)
Bacillus sphaericus UPMB10 is a plant growth promoting bacteria (PGPB) which enhances plant growth by acting as bioenhancer and biofertilizer. An oil palm cDNA microarray containing 2224 cDNA probes from root (partially derived from cDNA clones generated in this study), 828 from vegetative meristem and 696 from zygotic embryo was generated to investigate the transcriptomic changes in two-month-old in vitro oil palm (Elaeis guineensis Jacq.) (Deli x Yangambi) roots after inoculation with B. sphaericus UPMB10 for 120 h. This study was initiated with the generation of 1824 expressed sequenced tags (ESTs) from the roots of oil palm. A total of 1173 tentative unique genes (TUGs) were assembled from 1566 ESTs with readable sequences. However, only 984 TUGs showed significant matches (E-value less than 10-5) to the non-redundant protein database in the GenBank and they were further divided into 13 groups based on their putative functions. Subsequent microarray result showed that 151 and 125 transcripts were significantly up- and down regulated, respectively in the roots of oil palm inoculated with B. sphaericus UPMB10. Although transcripts involved in protein synthesis were increased and the expression level of auxin responsive genes were altered in B. sphaericus UPMB10-inoculated oil palms, there was no conclusive result to support the presence of auxin secreted by B. sphaericus UPMB10 in the medium. Despite the capability of B. sphaericus UPMB10 to fix atmospheric nitrogen, 120 h might not be sufficient for it to establish efficient nitrogen fixation to relieve possible N deficiency in oil palms. The plant-microbe interaction might also have alerted the defense system that led to the up-regulation of transcripts related to synthesis of hydrogen peroxide in oil palm. Verification of microarray result by real time RT-PCR showed that nine out of 11 candidate genes (81.8%) were consistent in their expression patterns. In conclusion, this study has provided a brief understanding of the transcriptomic changes in the oil palm roots inoculated with B. sphaericus UPMB10.